Manajemen Kurikulum di Madrasah Diniyah Nurul Ummah Kota Gede D.I. Yogyakarta - Mulyani Mudis Taruna (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
The problem which are the subject of current research is how to implementcurriculum management performed by Madrasah Diniyah Nurul Ummah (MDNU)and what supporting and obstructing factors in implementing the curriculummanagement. The objective of the reserach is to find out curriculum managementimplmented by MDNU and to understand supporting and obstructing factors in theirimplementation. Current research uses qualitative approach by using observations,in-depth interviews and documents / literature reviews to collect data. The resultsshow that in general curriculum management developed by MDNU is curriculum ina broader sense, in terms of objectives, contents, methods or learning processes andstrategies in learning evaluation system. However, in their implementation still holdits salaf tradition which is developing holy book in group into Qiroah Kitab, SoroganIndividu.Key words : Management, Curriculum, Madrasah Diniyah Nurul Ummah